Pengaruh Implementasi E-Procurement Terhadap Kinerja Rantai Pasok Dengan Inovasi, Integrasi Rantai Pasok Dan Hubungan Kemitraan Sebagai Mediator - Malau, Gerald Gilberd Vega (JWM (JURNAL WAWASAN MANAJEMEN), 2025)
This study aims to analyze the direct impact of e-procurement on supply chain performance, as well as its impact through the mediating roles of supply chain innovation, supply chain integration, and partner relationships. The research was conducted on employees of companies that use e-procurement as a tool for procuring goods and services. Data for the study was collected by distributing questionnaires to respondents located in the Jakarta area. The research design used is hypothesis testing, and the data analysis method employed to test the hypotheses is Structural Equation Modeling (SEM) using SmartPLS 4.0 software. The results of the study show that of the three mediating variables—supply chain innovation, supply chain integration, and partner relationships—none of these mediating variables demonstrated an impact of e-procurement on supply chain performance. Direct testing of the effect of e-procurement on these three mediating variables also revealed that e-procurement has a significant direct impact on supply chain innovation, supply chain integration, and partner relationships. Regarding the direct impact of these three mediating variables on supply chain performance, the results indicate that supply chain integration and partner relationships are able to drive supply chain performance. Meanwhile, supply chain innovation does not appear to play a role in improving supply chain performance.